Generalized Hyers-Ulam Stability of a System of Bi-Reciprocal Functional Equations (European Journal of Pure and Applied Mathematics, 2015)
In this paper, we nd the generalized Hyers-Ulam stability of thesystem of bi-reciprocal functional equationsr(x + u, y) = r(x, y)r(u, y)/[r(x, y) + r(u, y)];r(x, y + v) = r(x, y)r(x, v)/[r(x, y) + r(x, v)]in Frechet spaces.